Introduction to electrical engineering - Johnson, James H. (International Textbook Company, 1965)
This purpose of this book is to provide a mature approach to the subject of electrical engineering for studetns whose primary interests are in other areas of egineering. It provides a modern mathematical approach to circuits, electonics, computers and machinery